Data mining methods and applications - Lawrence, Kenneth D.; Kudyba, Stephan 1963-; Klimberg, Ronald K. (Auerbach Publications, 2008)
Addressing a variety of organizational issues, this book presents a compilation of research works on data mining and forecasting techniques, including multivariate, evolutionary, and neural net methods. It focuses on data mining techniques used for conducting marketing research